Fintech and financial inclusion: Opportunities and pitfalls - Thorsten Beck (Asian Development Bank Institute (ADBI), 2020)
Financial innovation in the form of new delivery channels, products, and providers has helped push out the frontier of access to finance and thus increase the bankable and banked population. Mobile money and crowdfunding platforms are prime examples for this. The same financial innovation has also blurred the regulatory boundaries of the financial system, with nonbanks, including telecom companies and bigtechs such as Alibaba and Tencent, taking to offering financial services and increasingly moving into the financial intermediation business. This paper summarizes recent research on (i) financial inclusion, with a focus on developments in Asia; (ii) the extent to which advances in financial inclusion are driven by digitally driven financial innovation; and (iii) what the rise of fintech and bigtech implies for the structure of the financial system. It draws regulatory conclusions from this research but also points to future research avenues.
Keywords: D14; G21; G23; G28; G41; G5; O16; 330; financial inclusion; financial innovation; fintech; bigtech; mobile money; big data